Dredging and sediment discharge in a river with floodplain. Physicochemical and microbiological effects in Paraná river - Maria Josefina Gonzalez; Stella Maris Gonzalez; Aldo Raul Paira; Pablo Agustín Collins (Heliyon)
Alterations caused by human activities in the environment, such as dredging, modify the physicochemical conditions and affect the habitat. Maintenance dredging that allows large vessels access to inland ports is a recurring disruptive action. The study aimed to evaluate, during a maintenance dredging operation in a port area of the Paraná River, the modifications in the structure of the river, the presence of contaminants and bacterial organisms. The effects caused during the operation of a suction dredge in a South America river under two temporal conditions were analyzed: i) the short and medium-term effects on the physicochemical variables, and ii) the immediate effects on the physicochemical variables and the abundance of bacterioplankton. The variables measured in sediment and water samples were limnological parameters (e.g. conductivity, pH, dissolved oxygen, among others), heavy metal concentration, presence of biocides, hydrocarbon molecules, nutrients, sediment granulometry, Escherichia coli, Enterococcus, total coliforms, and heterotrophic bacteria. Some physicochemical variables increased in the water column immediately after the water mass passed through the operating dredge, including sediment resuspension. The parameter changes were transient, as there were no significant increases in the variables downstream of the dredge during dredging and discharge operations or after dredging work. Some metal concentrations increased in the sediment and water column. Bacteria increased during dredging and more after rainfall events. Then, at the end of the dredging, the bacteria concentrations decreased to previous values. The possible effects of dredging disturbance were of the same order or less than those of natural ones, i.e. rainfall. Sixty days after the dredging work was completed, the system was back to normal both in the dredged and discharge areas.